Evaluation of emergency service nurses' patient handover and affecting factors: A descriptive study - Gungor, Serap; Akcoban, Sumeyye; Tosun, Betul (ELSEVIER SCI LTD)
Aim: The aim of the study was to determine the patient handover efficacy level of emergency room nurses and the influencing factors. Method: This descriptive, cross-sectional study was completed with (n = 120) emergency room nurses of two different state hospitals from April 26 to May 26, 2021. The "Nurses descriptive information form " and "Handover Evaluation Scale " were used as data collection forms. Results: The mean age of the nurses was 29.53(6.327 years, 70.8% of them were female, and 76.7% of them had a bachelor's degree. The mean number of handovers was 3.25 (SD = 3.17) for one nurse in a shift, and the mean handover duration for a patient was 10.16 (SD = 9.23) minutes. More than half of the nurses (61.7%) carried out oral handover at the bedside. The mean score of the handover evaluation scale was 53.31 (SD = 9.55). The mean score of the nurses who performed the handover with all the nurses on the shift (spelling and relieving) together was 56.47 (SD = 9.21) and higher than that of the nurses who performed the handover in small groups 49.84 (SD = 9.70), (p = 0.012). Conclusion: The results of this study may contribute to promoting patient safety and improving patient handover processes in emergency rooms. It is recommended that standardized and comprehensive written handover forms be used, that all emergency room nurses should attend the handover process, and that further observational and interventional studies should be conducted.
Keywords: Patient safety; Patient handover; Nursing; Emergency nursing